2018
DOI: 10.1021/acsami.7b19541
|View full text |Cite
|
Sign up to set email alerts
|

Rate-Limiting Step in Batteries with Metal Oxides as the Energy Materials

Abstract: Metal oxides are used as the energy materials in some aqueous and nonaqueous batteries. However, a large overpotential and poor rate-performance limit their wide application. Low electrical conductivity of the oxide is commonly considered to be the reason for these limitations. The present study specifically reveals the electrochemical reduction process of α-FeO particles by using a cyclic voltammetry technique combined with an electron spectroscopy technique. SEM and TEM observe the phase and crystal structur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 58 publications
0
9
0
Order By: Relevance
“…The experiment demonstrated that Cu or Cu 2 O is relatively stable in dry air. The overpotential for CuO reduction at −1.65 V is lower than the overpotential at −1.7 V, and the reaction rate of CuO reduction at −1.65 V is slower than that at −1.7 V. In the electrolytic cell, some residual O 2 from air unavoidably remained inside the electrolyte, even though the cell was purged with N 2 gas, 19 and O 2 reduction reaction could consume a part of the charge. The applied voltage was larger than the voltage of H 2 O decomposition (−1.23 V), and H 2 evolution on the cathode side also consumed a part of charge, even thought H 2 suppression additive was added.…”
Section: Resultsmentioning
confidence: 97%
“…The experiment demonstrated that Cu or Cu 2 O is relatively stable in dry air. The overpotential for CuO reduction at −1.65 V is lower than the overpotential at −1.7 V, and the reaction rate of CuO reduction at −1.65 V is slower than that at −1.7 V. In the electrolytic cell, some residual O 2 from air unavoidably remained inside the electrolyte, even though the cell was purged with N 2 gas, 19 and O 2 reduction reaction could consume a part of the charge. The applied voltage was larger than the voltage of H 2 O decomposition (−1.23 V), and H 2 evolution on the cathode side also consumed a part of charge, even thought H 2 suppression additive was added.…”
Section: Resultsmentioning
confidence: 97%
“…It was found, As shown in Figure 3a, inset charge state d, the charge product hexagonal nanoflakes is identified as Fe(OH) 2 by using HRTEM. [ 34,35 ] The single crystal of Fe(OH) 2 was observed and the interplanar spacing of (100), (010), and (−110) is 0.255 nm. The interplanar spacing of these planes is smaller than 0.282 nm from the standard PDF #13‐0089.…”
Section: Resultsmentioning
confidence: 99%
“…The application of XEDS mapping has become a feasible and effective way to discover elements' distribution in real space for energy materials. [52,53] In TEM, EELS collects transmission electrons and analyzes their energy distribution. Inelastic transmission electrons also contain electronic structure information inside the loss of energy.…”
Section: Energy Scalementioning
confidence: 99%